Dampak Pariwisata Pada Industri Kreatif: Suatu Kajian Literatur - Irawan, Edi (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2023)
Based on the results of the discussion in this study, it can be concluded that in order to examine more deeply the impact of tourism on the creative industry, it can be seen from two aspects, namely the creative industry. As for the creative industry aspect in tourism activities, it can be seen from the skills and talents of individuals who are full of a wealth of knowledge able to create jobs by exploiting intellectual property. Then in the aspect of the impact of the synergy of tourism and the creative industry can be seen in several things, namely: (1) Impact on the national economy, (2) Impact on the workforce, (3) Impact on increasing IPR, (4) Impact on the emergency of start ups, (5) Impact of increasing product export value, (6) Impact on cultural preservation, (7) Impact on social tolerance.